Association of rs1006737 in CACNA1C with alterations in prefrontal activation and fronto‐hippocampal connectivity. Issue 4 (13th February 2013) - Paulus, Frieder M.; Bedenbender, Johannes; Krach, Sören; Pyka, Martin; Krug, Axel; Sommer, Jens; Mette, Miriam; Nöthen, Markus M.; Witt, Stephanie H.; Rietschel, Marcella; Kircher, Tilo; Jansen, Andreas
<x xml:space="preserve">Abstract</x> Background: Genome‐wide association studies have identified the rs1006737 single nucleotide polymorphism (SNP) in the CACNA1C gene as a susceptibility locus for schizophrenia and bipolar disorder. On the neural systems level this association is explained by altered functioning of the dorsolateral prefrontal cortex (DLPFC) and the hippocampal formation (HF), brain regions also affected by mental illness. In the present study we investigated the association of rs1006737 genotype with prefrontal activation and fronto‐hippocampal connectivity. Methods: We used functional magnetic resonance imaging to measure neural activation during an n‐back working memory task in 94 healthy subjects. All subjects were genotyped for the SNP rs1006737. We tested associations of the rs1006737 genotype with changes in working‐memory‐related DLPFC activation and functional integration using a seed region functional connectivity approach. Results: Rs1006737 genotype was associated with altered right‐hemispheric DLPFC activation. The homozygous A (risk) group showed decreased activation compared to G‐allele carriers. Further, the functional connectivity analysis revealed a positive association of fronto‐hippocampal connectivity with rs1006737 A alleles. Conclusions: We did not replicate the previous findings of increased right DLPFC activation in CACNA1C rs1006737 A homozygotes. In fact, we found the opposite effect, thus questioning prefrontal inefficiency as rs1006737 genotype‐related intermediate phenotype. On the other hand, our results indicate that alterations in the functional coupling between the prefrontal cortex and the medial temporal lobe could represent a neural system phenotype that is mediated by CACNA1C rs1006737 and other genetic susceptibility loci for schizophrenia and bipolar disorder. Hum Brain Mapp 35:1190–1200, 2014. © 2013 Wiley Periodicals, Inc.